Effect of Muscle Denervation on Growth of Transplanted Tumor in Mice - Batkin, Stanley (1970)
A temporary retardation of transplanted Round Cell Neuroblastoma growth in the gastrocnemius muscle of mice was observed in 20% of the animals after denervation of the muscle. The tumor cells in these denervated animals showed structural alterations and deterioration in function. These altered cells when mixed with associated denervated muscle tissue, to which was added fresh tumor, produced a higher percentage of retardation upon subsequent transplants in innervated muscle.